Modulation of the cytokine profile in Caco-2 cells by faecal lactobacilli and bifidobacteria from individuals with distinct dietary habits. (February 2017) - Luongo, Diomira; Coppola, Annachiara; Treppiccione, Lucia; Bergamo, Paolo; Sorrentino, Alida; Ferrocino, Ilario; Turroni, Silvia; Neviani, Erasmo; Di Cagno, Raffaella; Cocolin, Luca; Rossi, Mauro
Highlights: Lactobacilli and bifidobacteria from three dietary human cohorts are examined. Both genera show anti-inflammatory properties on enterocytes. Enterocyte immunomodulation of lactobacilli is associated with a specific dietary habit. The geographical area has an impact on the immune activity of lactobacilli. Abstract: Enterocytes are actively involved in the defense against pathogens and they limit penetration of commensal microbes into tissues. They also have an important role in gut immunity as enterocytes confer mucosal dendritic cell specialisation. On the other hand, the microbiota is directly involved in the development and modulation of the intestinal immune system. Particularly, lactobacilli and bifidobacteria play a primary role in shaping the immune response. We further explored this issue by evaluating whether functional differences in Caco-2 cells could characterise faecal populations of lactobacilli (155 samples) and bifidobacteria (110 samples) isolated from three dietary cohorts (omnivores, ovo-lacto-vegetarians and vegans) recruited at four Italian centres (Turin, Parma, Bologna and Bari). According to our findings, tested bacteria were unable to modulate expression of IL-8, IL-10, TGF-β or thymic stromal lymphopoietin (TSLP) cytokines in unstimulated Caco-2 cells. Conversely, in phorbol 12-myristate 13-acetate and ionomycin (PMA/Io) stimulated Caco-2 cells, lactobacilli from the omnivorous group and all bifidobacteria significantly down-regulated IL-8. Notably, both genera also lowered the TSLP expression in stimulated Caco-2 cells, regardless of the diet regimen. By further examining these data on the basis of geographical origin, we found that lactobacilli from the vegetarian group recruited in Bari, significantly up-regulated this cytokine. In conclusion, we highlighted a peculiar immune-modulatory activity profile for lactobacilli on enterocytes undergoing a stimulatory signal, which was associated with a specific dietary habit. Furthermore, the geographical area had a significant impact on the inflammatory potential of members of the Lactobacillus genus.